2018
DOI: 10.1016/j.colsurfa.2018.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene fractionation based on adsorption onto calcium carbonate: Part 3. Effect of asphaltenes on wax crystallization

Abstract: Asphaltenes fractionation procedures were developed and tested in two preceding articles (doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 35 publications
(77 reference statements)
0
29
0
Order By: Relevance
“…The irreversibly adsorbed fraction, containing the highest concentration of carbonyl, carboxylic acid, or derivative groups was found to have a significantly higher tendency to self-associate and form larger aggregates than other fractions did, which exhibited similar properties with the fraction precipitating first from the sequential precipitation procedure [135]. The effect of these three asphaltene fractions on wax crystallization was also studied, and results showed that the irreversibly adsorbed fraction containing the most polar species induced the largest changes in wax-crystal morphology [136].…”
Section: Adsorption Onto Porous Mediummentioning
confidence: 88%
See 1 more Smart Citation
“…The irreversibly adsorbed fraction, containing the highest concentration of carbonyl, carboxylic acid, or derivative groups was found to have a significantly higher tendency to self-associate and form larger aggregates than other fractions did, which exhibited similar properties with the fraction precipitating first from the sequential precipitation procedure [135]. The effect of these three asphaltene fractions on wax crystallization was also studied, and results showed that the irreversibly adsorbed fraction containing the most polar species induced the largest changes in wax-crystal morphology [136].…”
Section: Adsorption Onto Porous Mediummentioning
confidence: 88%
“…Recently, a new fractionation procedure was developed on the basis of the adsorption of asphaltenes onto a porous medium, CaCO 3 . Three asphaltene fractions were obtained: the bulk (non-adsorbed) asphaltene that stayed in the bulk solution, the adsorbed asphaltene that was obtained by desorption of asphaltenes adsorbed on CaCO 3 using tetrahydrofuran, and the irreversibly adsorbed asphaltene that was obtained after CaCO 3 dissolution [134][135][136]. The irreversibly adsorbed fraction, containing the highest concentration of carbonyl, carboxylic acid, or derivative groups was found to have a significantly higher tendency to self-associate and form larger aggregates than other fractions did, which exhibited similar properties with the fraction precipitating first from the sequential precipitation procedure [135].…”
Section: Adsorption Onto Porous Mediummentioning
confidence: 99%
“…The fractionation process involved passing the asphaltene solution in toluene through a calcium carbonate packed bed column. 28 The most polar subfraction with the strongest affinity to the CaCO 3 surface is called irreversibly adsorbed (IA) asphaltenes (MW = 442), whereas the least polar asphaltenes that remain unadsorbed are called bulk asphaltenes (MW = 508). 29 The crude oil contained about 2.8 wt % asphaltenes, of which approx.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…The asphaltene subfractions used in this study are obtained by fractionation of whole asphaltenes extracted from a heavy crude oil from a Norwegian continental shelf. The fractionation process involved passing the asphaltene solution in toluene through a calcium carbonate packed bed column . The most polar subfraction with the strongest affinity to the CaCO 3 surface is called irreversibly adsorbed (IA) asphaltenes (MW = 442), whereas the least polar asphaltenes that remain unadsorbed are called bulk asphaltenes (MW = 508) .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Asphaltene samples and their subfractions were prepared at the Ugelstad Laboratory in NTNU. Asphaltenes were precipitated from a North Sea crude oil using n -hexane following the procedure described in ref . This will be further on referred to as the “whole asphaltenes” sample, whose results are discussed in the first part of the results section.…”
Section: Methodsmentioning
confidence: 99%